Characterisation of air permeability of common ceiling linings and penetrations. Issue 4 (12th August 2019) - Rupp, Stephan Harald; Plagmann, Manfred
Abstract : Purpose: Air permeability of ceiling linings is an important element in understanding air and moisture flux from living spaces into the roof cavity. Ideally, these two spaces are decoupled to avoid transportation of moist indoor air into the attic space, where it can lead to condensation on the cold roof cladding. The purpose of this paper is to experimentally characterise the air permeability of a variety of common ceiling types. The results are given as leakage functions. Characteristic leakage data are also given for several ceiling penetrations. A case study illustrates the relevance of these data. Design/methodology/approach: A specially designed test facility allows the installation of different ceiling types of up to 38 m 2 in area. Laminar flow elements are used to measure the volumetric flow across the ceiling while recording the pressure difference. The experimental data are fitted to the leakage function equation Q = c ( ΔP ) n . Ceiling penetrations are characterised in a similar way. For the case studies estimating the transport of moisture into the roof cavity, indoor climate data have been obtained using humidity and temperature sensors. Findings: Air leakage functions are given for a number of common ceiling linings and ceiling penetrations. These data can be used in simulations aimed at modelling moisture flux into the roof cavities. In the case study, the authors also give indoor climate data of residential dwellings in New Zealand. Originality/value: This paper addresses the need for robust ceiling air permeability data in whole-house temperature and moisture transport simulations.